Comparison of Bread Wheat Genotypes for Leaf Rust Resistance Genes - İSMET Başer (Journal of Agricultural Sciences, 2020)
Leaf rust caused by Pucinia recondita tritici is one of the most important diseases of bread wheat worldwide. It is considered that the most environmentally sound; low cost method of controlling leaf rust is to breed and grow genetically resistant wheat varieties. In the research, twenty-four bread wheat varieties grown intensively were used as genetic material in Trakya Region where the North-West Part of Turkey. To create artificial leaf rust epidemic in field conditions, two sensitive varieties (Morrocco and Cumhuriyet 75) was sown after each ten genotypes, and the reactions of the varieties to leaf rust were investigated in field conditions. Isogenic lines carrying the genes Lr9, Lr14, Lr19, Lr24 and Lr47 from CIMMYT were used as control genotypes in molecular analysis.In the field conditions, although Pehlivan, Selimiye, Sagittario, Tina, Anapo, Montchill and Saraybosna were the most sensitive genotypes, Nota, Kate A1, Prostor and Sana were the most resistant bread wheat varieties to leaf rust. It was determined that Sana, Pehlivan, Golia, Falmura 85, Saroz 95, Renan, Sirena, Kate A1, Selimiye, Bezostoja 1, Saraybosna, Nina and Tina varieties have Lr9 gene with SSR analysis. It has been observed that all bread wheat varieties carry Lr14, Lr19, Lr24 and Lr47 (except Krasunia, Aldane and Gelibolu varieties) genes.It is revealed that Lr9 and Lr47 genes should be taken into consideration in the studies to be performed in the region and these genes will be useful to examine together with a larger number of leaf rust genes for more successful results in breeding studies.